DETERMINANTS OF EARLY ADOPTION OF FRS 114 (SEGMENT REPORTING) IN MALAYSIA - Wan Nordin Wan Hussin,; Noriah Che Adam,; Noriah Che Adam,; Nor Asma Lode, (Asian Academy of Management Journal, 2005)
This study seeks to find out whether there are systematic differences between early adopters and a matched control group of non early adopters of FRS 114 (Segment Reporting) based on the following company characteristics: (1) firm size, (2) board characteristics, (3) leverage, (4) audit firm size, and (5) firm growth rate. Using a sample of 32 early adopters and without differentiating whether they disclose the required segment information in full or partially and a control group of 32 non early adopters, our findings indicate company with higher proportion of non executive directors, particularly non independent non executives, is more likely to adopt FRS 114 before the effective date. When early adopters are further classified into full or partial adopters, the result shows that full early adopters are significantly larger (in terms of total assets) than non early adopters. However, when comparing between partial early adopters and non early adopters, the evidence suggests that partial early adopters are significantly smaller in size than non early adopters. We find no evidence to indicate that there are significant differences between full early adopters, partial early adopters and non early adopters in terms of board size, board leadership, independent directors, audit firm size, leverage and firm growth rate.